Shear deformation dominates in the soft adhesive layers of the laminated structure of flexible electronics. (April 2017) - Li, Shuang; Liu, Xiaoli; Li, Rui; Su, Yewang
Abstract: Flexible electronics has attracted much attention in recent years due to the favorable applications to many emerging devices. A novel laminated structure for a new-generation of flexible electronics is composed of several thin layers, where the hard functional components are built, glued by soft adhesives. To prevent the premature mechanical failure and to achieve the best performance of the electronics, the structural design of such a laminate is of crucial importance. Accordingly, it is necessary to establish an analytic model to accurately describe the mechanical behavior of the laminated structure. The available models fall into two categories: those only taking into account the normal strain-induced deformation of the soft adhesive layers and those only incorporating the shear deformation of the same layers. This paper aims to quantitatively figure out which deformation dominates. By establishing an accurate enough analytic model, a significant finding is revealed that shear deformation dominates in the soft adhesive layers of the laminated structure of flexible electronics while the normal strain-induced deformation is negligible. The model is well validated by the finite element method (FEM). The effects of the membrane energy and bending energy of the soft layer are also investigated by incorporating or neglecting the shear energy. The model accurately captures the key quantities such as the strain distribution in each layer and the locations of the neutral mechanical planes of the top and bottom layers. This work is expected to provide the design guidelines for the laminated structure-based flexible electronics.